2012
DOI: 10.1371/journal.pone.0045535
|View full text |Cite
|
Sign up to set email alerts
|

Unveiling Clusters of RNA Transcript Pairs Associated with Markers of Alzheimer’s Disease Progression

Abstract: BackgroundOne primary goal of transcriptomic studies is identifying gene expression patterns correlating with disease progression. This is usually achieved by considering transcripts that independently pass an arbitrary threshold (e.g. p<0.05). In diseases involving severe perturbations of multiple molecular systems, such as Alzheimer’s disease (AD), this univariate approach often results in a large list of seemingly unrelated transcripts. We utilised a powerful multivariate clustering approach to identify clu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
17
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(21 citation statements)
references
References 119 publications
4
17
0
Order By: Relevance
“…Consistent with our report, RanBP9 was recently found to be within the clusters of RNA transcript pairs associated with markers of AD progression (Arefin et al, 2012), supporting our idea that RanBP9 might play a critical role in the pathogenesis of AD. Our subsequent investigations using transgenic mice overexpressing RanBP9 confirmed that RanBP9 in fact regulates Aβ generation and amyloid plaque burden in vivo in the mouse brain.…”
Section: Introductionsupporting
confidence: 92%
“…Consistent with our report, RanBP9 was recently found to be within the clusters of RNA transcript pairs associated with markers of AD progression (Arefin et al, 2012), supporting our idea that RanBP9 might play a critical role in the pathogenesis of AD. Our subsequent investigations using transgenic mice overexpressing RanBP9 confirmed that RanBP9 in fact regulates Aβ generation and amyloid plaque burden in vivo in the mouse brain.…”
Section: Introductionsupporting
confidence: 92%
“…The RanBP9-LisH Domain Binds COPS5 in the Yeast Twohybrid System-Recently, RanBP9 was found to be within the clusters of RNA transcript pairs associated with markers of AD progression, suggesting that RanBP9 might play a pathogenic role in AD (9). In fact, down-regulation of RanBP9 significantly reduced A␤ generation in primary neuronal cultures (11), implying that RanBP9 regulates A␤ generation.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, RanBP9 was found to be within the clusters of RNA transcript pairs associated with markers of AD progression, suggesting that RanBP9 might contribute to the pathogenesis of AD (9). In fact, even before this finding, we showed for the first time that RanBP9 protein levels are increased 6-fold in AD brains (10) and that RanBP9 overexpression increases A␤ generation 4-fold in cell cultures by increasing ␤-secretase-mediated processing of APP (11) and also increases amyloid plaques in mouse brains (12), which, in turn, leads to a significant loss of synaptic proteins (12).…”
Section: Alzheimer's Disease (Ad)mentioning
confidence: 99%
“…RanBP9 is a multidomain protein that functions as a scaffolding protein by assembling multiprotein complexes in different subcellular regions, thereby mediates diverse cellular functions (Murrin and Talbot, 2007; Suresh et al, 2012). Recently, RanBP9 was found to be within the clusters of RNA transcript pairs associated with markers of AD progression (Arefin et al, 2012), suggesting that RanBP9 might contribute to the pathogenesis of AD. In fact, even before this discovery, we showed for the first time that RanBP9 increased Aβ generation by 4-fold in a variety of cell cultures (Lakshmana et al, 2010), primary neurons (Lakshmana et al, 2009) as well as mouse brains (Lakshmana et al, 2012), consequently leading to increased amyloid plaque burden (Lakshmana et al, 2012).…”
Section: Introductionmentioning
confidence: 99%